Dynamical effects in the vibrationally resolved C 2s-1 photoionization cross section ratios of Methane. (August 2015) - Nandi, Saikat; Patanen, Minna; Miron, Catalin; Bozek, John D; Plésiat, Etienne; Martin, Fernando; Toffoli, Daniele; Decleva, Piero
Synopsis: The vibrationally resolved C 2s photoionization cross-section of methane was investigated both theoretically and experimentally. When compared to that of C 1s photoionization, a rather different pattern has been observed, suggesting a strong interplay between the electron diffraction and interference effects.